Age‐dependent alterations to paraventricular nucleus insulin‐like growth factor 1 receptor as a possible link between sympathoexcitation and inflammation. Issue 5 (19th October 2016) - Ogundele, Olalekan M.; Lee, Charles C.; Francis, Joseph
Abstract: Modifications to neural circuits of the paraventricular hypothalamic nucleus (PVN) have been implicated in sympathoexcitation and systemic cardiovascular dysfunction. However, to date, the role of insulin‐like growth factor 1 receptor (IGF‐1R) expression on PVN pathophysiology is unknown. Using confocal immunofluorescence quantification and electrophysiological recordings from acute PVN slices, we investigated the mechanism through which age‐dependent IGF‐1R depletion contributes to the progression of inflammation and sympathoexcitation in the PVN of spontaneously hypertensive rats (SHR). Four and twenty weeks old SHR and Wistar Kyoto (WKY) rats were used for this study. Our data showed that angiotensin I/II and pro‐inflammatory high mobility box group protein 1 (HMGB1) exhibited increased expression in the PVN of SHR versus WKY at 4 weeks ( p < 0.01), and were even more highly expressed with age in SHR ( p < 0.001). This correlated with a significant decrease in IGF‐1R expression, with age, in the PVN of SHR when compared with WKY ( p < 0.001) and were accompanied by related changes in astrocytes and microglia. In subsequent analyses, we found an age‐dependent change in the expression of proteins associated with IGF‐1R signaling pathways involved in inflammatory responses and synaptic function in the PVN. MAPK/ErK was more highly expressed in the PVN of SHR by the fourth week ( p < 0.001; vs. WKY), while expression of neuronal nitric oxide synthase ( p < 0.001) and calcium‐calmodulin‐dependent kinase II alpha (CamKIIα; p < 0.001) were significantly decreased by the 4th and 20th week, respectively. Age‐dependent changes in MAPK/ErK expression in the PVN correlated with an increase in the expression of vesicular glutamate transporter ( p < 0.001 vs. WKY), while decreased levels of CamKIIα was associated with a decreased expression of tyrosine hydroxylase ( p < 0.001) by the 20th week. In addition, reduced labeling for ϒ‐aminobutyric acid in the PVN of SHR ( p < 0.001) correlated with a decrease in neuronal nitric oxide synthase labeling ( p < 0.001) when compared with the WKY by the 20th week. Electrophysiological recordings from neurons in acute slice preparations of the PVN of 4 weeks old SHR revealed spontaneous post‐synaptic currents of higher frequency when compared with neurons from WKY PNV slices of the same age ( p < 0.001; n = 14 cells). This also correlated with an increase in PSD‐95 in the PVN of SHR when compared with the WKY ( p < 0.001). Overall, we found an age‐dependent reduction of IGF‐1R, and related altered expression of associated downstream signaling molecules that may represent a link between the concurrent progression of synaptic dysfunction and inflammation in the PVN of SHR. Abstract : We highlighted a possible mechanism through which an age‐dependent change in IGF‐1R/ CamKIIα expression causes a simultaneous progression of inflammation and sympathoexcitation in the paraventricular nucleus of spontaneously hypertensive rats. Taken together, we found that the loss of IGF‐1R/ CamKIIα in the SHR, was associated with an increase in pro‐inflammatory MAPK/ErK and HMGB1. Additionally, we recorded a decrease in GABA, and an elevated level of VGLUT 2/Tyrosine hydroxylase. Our results suggest a crucial role for IGF‐1R/CamKIIα in the pathophysiology of PVN sympathoexcitation.